Epidemiology of Upper-Extremity Amputations Using the National Electronic Injury Surveillance System. Issue 5 (June 2021) - Cramer, Jordan; Brown, Geoffrey; Herrera, Fernando A.
Abstract : Background: Upper-extremity amputations can be devastating injuries that lead to lifelong disabilities. The purpose of our study was to review national data and identify populations at risk and injury patterns that could be targeted with prevention strategies. Methods: Data from the National Electronic Injury Surveillance System between years 2012 and 2018 were reviewed. Injuries affecting the upper extremity resulting in amputation were included. Patient demographics, anatomical location, mechanism of injury, level of care provided, and setting of injury were recorded. Descriptive was recorded and tabulated for each category. Results: There were 4, 766 patients identified with amputations to the upper extremity from 2012 to 2018. The following categories are listed below: age in years, sex, race, anatomical location of injury, most common mechanisms of injury, disposition of patient, environmental location. Conclusions: Our data show that male children younger than 10 years are at the high risk for finger amputations. In addition, the majority of these injuries occur in the home. This suggests that safety prevention in the home is a significant area in need of improvement. We recommend further research in areas of home safety and injury prevention to decrease the risk of the devastating injuries.